The role of BATF in immune cell differentiation and autoimmune diseases - Xiaomeng Wang; Yue Hong; Jinmei Zou; Bo Zhu; Chao Jiang; Liwei Lu; Jie Tian; Jing Yang; Ke Rui (Biomarker Research)
Abstract As a member of the Activator Protein-1 (AP-1) transcription factor family, the Basic Leucine Zipper Transcription Factor (BATF) mediates multiple biological functions of immune cells through its involvement in protein interactions and binding to DNA. Recent studies have demonstrated that BATF not only plays pivotal roles in innate and adaptive immune responses but also acts as a crucial factor in the differentiation and function of various immune cells. Lines of evidence indicate that BATF is associated with the onset and progression of allergic diseases, graft-versus-host disease, tumors, and autoimmune diseases. This review summarizes the roles of BATF in the development and function of innate and adaptive immune cells, as well as its immunoregulatory effects in the development of autoimmune diseases, which may enhance the current understanding of the pathogenesis of autoimmune diseases and facilitate the development of new therapeutic strategies.